Kualitas Corporate Governance dan Kinerja Bank: Studi Kasus Perbankan di Indonesia - Sumanti, Elvis (JBE (Journal of Business and Economics); Volume 11 No.1, 2012 JBE UNKLAB, 2012)
This research aims to analyze the significance of the quality of the implementation of corporate governance toward bank financial performance as measured by CAMEL. Statistic method used to examine the significance is simple linear regression. The object of the research is listed banks on Indonesia Stock Exchange from 2006-2010 that meet the pre-determined sampling characteristics. The result of the study finds that the quality of corporate governance implementation as measured by corporate governance index does not affect listed bank performance